(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
This paper aims to examine the Pattani dialect in Perak. The impact of the migration of a large number of people from Pattani province due to ongoing war brought with it a subdialect in Perak known as the Pattani dialect. Field research on 22 villages carried out in Larut Matang Selama, Kuala Kangsar and Hulu Perak, involving 156 respondents proved the existence of this dialect. This study employed the Geographical Information System (GIS) that relates geography and linguistics, or geolinguistics. The distribution of this dialect is linked to factors such as area and topography. Earlier on, the Pattani people settled near by the mountains for security, while nowadays they have become more open and have moved to the lowlands around Lenggong, where they interact with the locals. This encounter has formed new lexical items such as [muh̃a] for "you all", and [banta] for "pillow", as well as loanwords such as [p h] from "opah" (grandmother). Interestingly, we found loanwords from the Perak dialect being used quite extensively in the Pattani dialect. Keywords: Pattani, GIS, dialect, area, geolinguistics, distribution